Pengaruh Model Talking Stick Terhadap Kemampuan Menganalisis Unsur Intrinsik Puisi ODE Pada Siswa Kelas VIII SMP Negeri 1 Cigeulis - Meliyawati Meliyawati; Asep Sahrudin (Universitas Mathla'ul Anwar Banten, 2018)
The method used in this study in an experimental method conducted in State Junior High School 1 Cigeulis Pandeglang regency by taking eight grade student in the academic year 2017/2018 as a population. As for the sample technique using classter random sampling. Lottery results for the five classes that were obtained werw class VIII-A as the experimental class and class VIII-B as the control class. Each class numbered 25 students. This the number of samples in this study was 50 students. Class A is given a talking stick model, while class B control is given an expository model. Based on testing the hypothesis it can be concluded that there is a positive influence on the use of the talking stick model on the ability to analyze the intrinsic element of ode poetry class VIII 1 Cigeulis middle school Pandeglang District Bnaten Academic Year 2017/2018. This result is based on t testing at the significance level α = 0,05 obtaine tcount = 9,225 ttable = 1,6814 with error rates 5% and dk = 48, then obtaine tcount > ttable. Yhus the value of decision H0 rejected (μ1 ≠ μ2) wich means significantly that there is an effect of using the talking stick model on the ability to analyze elements of ode poetry in class VIII junior high school 1 Cigeulis Pandeglang district Academic Year 2017/2018